ALGORITMA SINGLE PASS CLUSTERING UNTUK KLASTERING HALAMAN WEB :Prosiding Seminar Nasional Komputer dan Elektro (SENOPUTRO) 2012 (Publikasi Eksternal, 2012)
The process of information retrieval with the internet is often get information very much, but most of information are unneeded. From the viewpoint of information retrieval, a number of information available on the internet more than difficult to get the relevant information, the information that feasible with we needs.This research to cluster documents using Single Pass Clustering Algorithm. This research is emphasized to clustering the Indonesian documents. Links between documents is measured by the simmilarity between the documents. The algorithm was tested with the use of online news archives news documents in HTML format http://www.kompas.com/archive Compass.Test results show that this algorithm can be applied to the grouping of Indonesian documents . The selection of the right keywords will increase the quality of information retrieval in the documents.disampaikan di Seminar Nasional Komputer dan Elektro (SENOPUTRO) 2012 - Fakultas Teknik Universitas Surakarta  tanggal 10 Maret 2012